1998
DOI: 10.1128/mcb.18.4.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Light and Heat on the Drosophila Circadian Clock Proteins PER and TIM

Abstract: Circadian (Х24-h) rhythms are governed by endogenous biochemical oscillators (clocks) that in a wide variety of organisms can be phase shifted (i.e., delayed or advanced) by brief exposure to light and changes in temperature. However, how changes in temperature reset circadian timekeeping mechanisms is not known. To begin to address this issue, we measured the effects of short-duration heat pulses on the protein and mRNA products from the Drosophila circadian clock genes period (per) and timeless (tim). Heat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 53 publications
2
88
0
Order By: Relevance
“…(3) Finally, hisCl1 is expressed in circadian clock neurons. Recently, several reports showed that changes in environmental temperature could directly control the circadian clock (Sawyer et al, 1997;Sidote et al, 1998;Majercak et al, 1999;Glaser and Stanewsky, 2005). In addition, our previous data suggested that clock neurons can affect temperature preference in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…(3) Finally, hisCl1 is expressed in circadian clock neurons. Recently, several reports showed that changes in environmental temperature could directly control the circadian clock (Sawyer et al, 1997;Sidote et al, 1998;Majercak et al, 1999;Glaser and Stanewsky, 2005). In addition, our previous data suggested that clock neurons can affect temperature preference in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…Preparations of head extracts and protein blots were performed by using anti-PER and -TIM as well as dilutions of these antibodies, as described (5), except that for the blots shown in Fig. 5, a different anti-TIM antibody was applied (31).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, separate aliquots of cells were incubated for 24 hours at different temperatures in the dark. Total RNA was extracted, and the relative levels of spliced and nonspliced products were determined as previously described using reverse transcriptase-polymerase chain reaction (RT-PCR) whereby values are normalized to an internal RNA standard (Majercak et al 2004). The dmpi8 control RNA exhibited approximately 2.5-3.2-fold increases (n > 10; P <0.001 using Student's t-test for values obtained at 12°C and 24°C) in the proportion of spliced-to-unspliced RNA at 12°C compared to 24°C (Fig.…”
Section: A Role For Thermal-sensitive Splicing Of a Clock Gene In Seamentioning
confidence: 99%
“…Although period length is rather insensitive to temperature fluctuations, the phases and amplitudes of circadian rhythms can exhibit clear temperature-induced changes. Most notably, circadian rhythms can be phase-shifted by changes in temperature (pulses and step-up or -down) and entrained by daily temperature cycles (see, e.g., Sweeney and Hastings 1961;Wheeler et al 1993;Liu et al 1997Liu et al , 1998Sidote et al 1998;and references therein). Other work indicates that the amplitude of a circadian oscillator changes as a function of temperature (usually perceived as increasing with rising temperature), suggested by some as a solution to temperature compensation of period length (LakinThomas et al 1991;Pittendrigh et al 1991).…”
Section: Introductionmentioning
confidence: 99%